Organogenesis in vitro. (December 2021) - Iwasawa, Kentaro; Takebe, Takanori
Abstract: Organoids are three-dimensional structures that self-organize from human pluripotent stem cells or primary tissue, potentially serving as a traceable and manipulatable platform to facilitate our understanding of organogenesis. Despite the ongoing advancement in generating organoids of diverse systems, biological applications of in vitro generated organoids remain as a major challenge in part due to a substantial lack of intricate complexity. The studies of development and regeneration enumerate the essential roles of highly diversified nonepithelial populations such as mesenchyme and endothelium in directing fate specification, morphogenesis, and maturation. Furthermore, organoids with physiological and homeostatic functions require direct and indirect inter-organ crosstalk recapitulating what is seen in organogenesis. We herein review the evolving organoid technology at the cell, tissue, organ, and system level with a main emphasis on endoderm derivatives.